Frailty and Its Associated Risk Factors: First Phase Analysis of Multicentre Indonesia Longitudinal Aging Study - Setiati, Siti; Soejono, Czeresna Heriawan; Harimurti, Kuntjoro; Dwimartutie, Noto; Aryana, I. G. P. Suka; Sunarti, Sri; Budiningsih, Fatichati; Mulyana, Roza; Dwipa, Lazuardhi; Sudarso, Agus; Rensa, Rensa; Istanti, Rahmi; et al. (Frontiers in Medicine, 2021)
Background: National long-term care development requires updated epidemiological data related to frailty. We aimed to find the prevalence of frailty and its associated factors among Indonesian elderly. Methods: We conducted first-phase cross-sectional analysis of Indonesia Longitudinal Ageing Study (INALAS) data collected from community-dwelling outpatients aged 60 years and older without acute illness in nine geriatric service care centres. Descriptive, bivariate and multivariate analyses were conducted. Results: Among 908 elderly in this study, 15.10% were robust, 66.20% were pre-frail, and 18.70% were frail. Functional dependence was associated with frailty among Indonesian elderly (OR 5.97, 95% CI 4.04 to 8.80). Being depressed and at risk for malnutrition were also associated with frailty with OR 2.54, 95% CI 1.56 to 4.12, and OR 2.56, 95% CI 1.68 to 3.90, respectively. Prior history of fall (OR 1.77, 95% CI 1.16 to 2.72) and hospitalisation (OR 1.46, 95% CI 0.97 to 2.20) in the previous 12 months were associated with frailty. There is also significant association between polypharmacy and frailty (OR 2.42, 95% CI 1.50 to 3.91). Conclusion: Approximately one in five Indonesian community-dwelling elderly was frail. Frailty is associated with functional dependence, being at risk for malnutrition or being malnourished, depression, history of fall, history of hospitalisation, and polypharmacy. There may be bidirectional relationships between the risk factors and frailty. The development of long-term care in Indonesia should be considered, without forcing the elderly who need it.